2014 IEEE Haptics Symposium (HAPTICS) 2014
DOI: 10.1109/haptics.2014.6775521
|View full text |Cite
|
Sign up to set email alerts
|

A simplified approach to admittance-type haptic device impedance evaluation

Abstract: Evaluating the transparency, or output impedance more generally, of admittance-type haptic devices is challenging due to their inherently non-back-drivable mechanical characteristics. To address this, we describe a new, simplified evaluation approach that eliminates the need for external test fixtures. The simplified approach relies on the easily obtainable closed-loop position control response of the device in combination with a device/system dynamic model. In addition to evaluating output impedance, the appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…In the literature, admittance type devices are rarely seen as haptic systems, however it is mandatorily used as haptic system when there are mechanical limitations such as high inertia, high friction and as a consequence of these, non-backdrivability. The admittance type haptic systems are mostly preferred in surgical operations [4,5], rehabilitation systems [6,7], industrial operations [8,9] and haptic researches [10,11].…”
Section: Overview Of Admittance Type Haptic Systemsmentioning
confidence: 99%
“…In the literature, admittance type devices are rarely seen as haptic systems, however it is mandatorily used as haptic system when there are mechanical limitations such as high inertia, high friction and as a consequence of these, non-backdrivability. The admittance type haptic systems are mostly preferred in surgical operations [4,5], rehabilitation systems [6,7], industrial operations [8,9] and haptic researches [10,11].…”
Section: Overview Of Admittance Type Haptic Systemsmentioning
confidence: 99%
“…Peer [3] also concluded that the firm operator grasp aghil.jafari@uwe.ac.uk makes the admittance haptic interfaces unstable. Parthiban [4] proposed a method to evaluate the stable rendering range of the admittance-type haptic displays. Nambi [5] analyzed the effect of velocity, admittance gain, and force on human force control ability.…”
Section: Introductionmentioning
confidence: 99%